Sulfur-anchored azulene as a cathode material for Li–S batteries. Issue 61 (11th July 2019) - Chen, Zhenying; Droste, Jörn; Zhai, Guangqun; Zhu, Jinhui; Yang, Jun; Hansen, Michael Ryan; Zhuang, Xiaodong
Abstract : A benzene-free and vinyl-free molecule, azulene, is used to polymerize with sulfur for new cathode material based Li–S batteries. Abstract : A benzene-free and vinyl-free molecule, azulene, is used to polymerize with sulfur through inverse vulcanization. The sulfur radical promoted reaction mechanism has been studied through solid-state NMR experiments combined with DFT calculations. The as produced polymer has high sulfur content and can serve as a cathode material for Li–S batteries with longer lifetime stability compared to pure sulfur, providing a new protocol to develop new cathode materials for Li–S batteries.